(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The digital age has brought about significant changes in various aspects of human life, includingthe legal system. One such area that has seen considerable evolution is the process of grantingbail. With the advent of electronic records and digital evidence, courts now have the capability tomaintain records of bail in electronic form. This advancement presents both opportunities andchallenges for the judiciary. The ease of access and manipulation of electronic documents raisesconcerns about the legitimacy and admissibility of electronic evidence in court. Furthermore, thespecialized nature of electronic evidence requires distinct methodologies for investigation andanalysis, which necessitates expert training in the field of cyberspace. This paper explores theevolution of bail in the digital age, focusing on the challenges and implications for the judiciary,including the handling of electronic evidence, the role of sureties, and the conditions imposed bycourts after granting bail.